The Effect Of COVID-19 Pandemic On Smes Management In Jordan - Nawaiseh, Dr. kafa Hmoud (The journal of contemporary issues in business and government, 2021)
The effect of COVID-19 pandemic was severe in most countries and in all sectors. The vulnerable is the SMEs. The objective of this study is to investigate the management response of SMEs for the difficulties they face through the pandemic. Qualitative research was used. The questionnaire was used as a tool to collect data. The questionnaire was designed to collect information about the demographic characteristic of SMEs owners, the operational difficulties, the financial difficulties and the management response to COVID-19. The questionnaire was distributed on a random sample of SMEs composed of 1321 owners. The questionnaire was distributed using electronic tools. The collected data was analyzed using SPSS. The results showed that SMEs owners faced many operational difficulties (workers overload, low production, customers interests change, and low flow of raw material) and financial difficulties (low sales, low cash flow, and low turnover). The highest management response by SMEs owners was through minimizing the workers wages to 50%, to register in Social Security Foundation to support their workers, decrease the expenses and the stored stocks.